Metaphoric Expression of Allusion in the Headlines of French Political Articles - Tolstolutskaya, Evguenya V.; Mikhailova, Elena N.; Sleptsova, Svetlana V.; Svischev, Guennady V.; Kuzmina, Oksana V. (Journal of History Culture and Art Research, 2018)
The article analyzes metaphorical constructions expressing the hint. The study is carried out on the basis of the political article headlines of contemporary prestigious French editions of “Monde diplomatique”, “Le Figaro”, “Télérama”. The hint is regarded as an indirect speech act reflecting the meaning of information implicitly. The classification of article headlines is based on the metaphors types: "Anthropomorphic metaphor", "Metaphor of nature", "Social metaphor", "Artifact metaphor" and "Metaphor of irreality". Each type of metaphor is considered in connection with the conceptual spheres related to it. The study showed that in the language of modern French press there is a great number of headline structures containing: "Anthropomorphic metaphor" with such conceptual spheres as "Anatomy and physiology", "Disease", "Family"; "Metaphor of nature" with such concepts as "Animal world", "Plant world"; "Social metaphor", the sources of this metaphorical expansion are such conceptual spheres as "Crime", "War", "Theater", "Game and sport"; "Artifact metaphor" with the concepts "House" and "Mechanism".